The Comparison Between Parents’ Educational Background with Students’ Ability in Mastering English Vocabulary at SMP Negeri 2 Siborongborong - Rekolina Siahaan; Novita C. Hutabarat (International Journal of Educational Technology and Society, 2024)
The objective of the research to investigate The Comparison Between Parents’ Educational Background with Students’ Ability in Mastering English Vocabulary. The sources of the data for the subject were 40 students of SMP Negeri 2 Siborongborong. The research take 25% as a sample. This research was use descriptive quantitative method. The data was obtained by administering the test. The data were process by applying test. It is found that the hypothesis is accepted. This implicit that the students’ who have high parents’ educational background is better than the low parents’ educational background.